+0  
 
0
462
2
avatar

2x^2-x+5,g(x)=x+1

find (f+g)(x) and (f+g)(6)

Guest Oct 29, 2014

Best Answer 

 #2
avatar+92763 
+5

2x^2-x+5,g(x)=x+1    assuming that the first function is f(x)

[f+g](x) means that we just add the functions together  = 2x^2 + 6

[f + g](6)  means that we "plug" 6 into what we've just found in the first part......so we have...... 2(6)^2 + 6  = 2(36) + 6 = 72 + 6 = 78

 

CPhill  Oct 29, 2014
 #1
avatar+17746 
+5

f(x)  =  2x² - x + 5                 g(x)  =  x + 1

(f + g)(x)  =  f(x) + g(x)  =   (2x² - x + 5) + (x + 1)  =  2x² + 6

(f + g)(6)  = 2(6²) + 6  =  78

geno3141  Oct 29, 2014
 #2
avatar+92763 
+5
Best Answer

2x^2-x+5,g(x)=x+1    assuming that the first function is f(x)

[f+g](x) means that we just add the functions together  = 2x^2 + 6

[f + g](6)  means that we "plug" 6 into what we've just found in the first part......so we have...... 2(6)^2 + 6  = 2(36) + 6 = 72 + 6 = 78

 

CPhill  Oct 29, 2014

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.